2015
DOI: 10.1007/s11356-015-5981-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on usage of plastic oil and B20 algae biodiesel blend as substitute fuel to diesel engine

Abstract: Usage of plastics has been ever increasing and now poses a tremendous threat to the environment. Millions of tons of plastics are produced annually worldwide, and the waste products have become a common feature at overflowing bins and landfills. The process of converting waste plastic into value-added fuels finds a feasible solution for recycling of plastics. Thus, two universal problems such as problems of waste plastic management and problems of fuel shortage are being tackled simultaneously. Converting wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…CO 2 and unburned hydrocarbon were found higher with usage of plastic fuel. Smoke quantity was also increased with WPO .…”
Section: Introductionmentioning
confidence: 88%
“…CO 2 and unburned hydrocarbon were found higher with usage of plastic fuel. Smoke quantity was also increased with WPO .…”
Section: Introductionmentioning
confidence: 88%
“…Transesterification is an organic procedure of altering bid branched triglyceride molecules of plant fats and oils into minor molecules of straight chain, just like the size of diesel fuel molecules. This method takes place due to the reaction between alcohol (Methanol-CH 3 OH) and vegetable oil under the impact of the catalyst (NaOH or KOH) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: A Biodiesel Preparationmentioning
confidence: 99%
“…The earlier work of numerous academics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] has described that, the biodiesel blend with predictable diesel has significantly decrease the deplete emissions and rises the performance of engine. The biodiesels obtained till now are not sufficient to encounter the worldwide requirement of fuel therefore exploring other possible sources as an auxiliary for conservative fuels is a requirement.…”
Section: Introductionmentioning
confidence: 99%
“…The reports show that the engine performance can be improved by blending waste plastic oil to heavy oil used in marine applications [Ioannis S. A and P Tserkezou 2008]. Experiments on plastic oil and B20 algae blend were conducted by Ramesh et al It was observed by the authors that the brake thermal efficiency of B20 was 15.7% higher than that of conventional diesel fuel [Ramesh et al 2016]. Therefore, the literature strongly supports the functional suitability of plastic pyrolysis oil in a compression ignition engine and, if properly understood, it can substitute diesel in near future.…”
Section: Plastic Pyrolysis: An Alternativementioning
confidence: 99%